Pengaruh Frekuensi Perdagangan, Volume Perdagangan Dan Kapitalisasi Pasar Terhadap Return Saham Sektor Pertambangan Batu Bara Yang Terdaftar Di BEI - Yuana Yuana; Juliahir Barata (REVITALISASI : Jurnal Ilmu Manajemen, 2022)
This study aims to analyze the effect of trading frequency, trading volume and market capitalization on stock returns in the Coal Mining sector listed on the Indonesia Stock Exchange. The sample in this study amounted to 4 companies selected using the purpose sampling method. The analytical tool used is SPSS version 23. Based on the analysis that has been done, the results show that trading frequency has a significant effect on stock returns. Trading volume has a significant effect on stock returns. Market capitalization has a significant effect on stock returns. The magnitude of the influence of the independent variable can affect the dependent variable, which is 45.5% and the remaining 54.5% is influenced by other factors that are not included in the research model.